Curriculum Management Forming Entrepreneur Character Students In Bina Ulama Islamic Boarding School Kisaran Asahan - Mesiono, Humaidah Br Hasibuan, M. Akhyar (International Journal Of Education, Social Studies, And Management (IJESSM), 2021)
This study aims to find out how Curriculum Management in Shaping the Entrepreneurial Character of Santri in Islamic Boarding School Bina Ulama Kisaran Asahan. The method of research that is used is the research field (field research) that is qualitative phenomenology. Results of the study were obtained are planning curriculum At the Bina Ulama Islamic Boarding School, Kisaran is every student who has been accepted at the Boarding School, the foundation will introduce various extracurricular activities in the Boarding School, especially in the entrepreneurial extracurricular activities section. Then for students who are interested in participating in entrepreneurial extracurricular activities, the mu'allim or mu'allima who is in charge will guide and motivate these students. Organizing for the Bina Ulama Islamic Boarding School in Kisaran Asahan is important because with the organization the foundation will be easier to control and evaluate in each field, especially in the field of entrepreneurial activity. Implementation of the curriculum in shaping the character of entrepreneur students in boarding schools Bina Ulama Asahan range there are two phases of practice and theory, but here by mu'allim or mu'allimah as the person responsible for part of entrepreneurship over emphasize practice than in theory. Evaluations were conducted every month by Bina Ulama Boarding School to know what progress and what barriers were faced by those responsible for the respective field of entrepreneurial activities that will be better again.